2007
DOI: 10.2475/06.2007.01
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of gas hydrate distribution and saturation in marine sediments by scaling of thermodynamic and transport processes

Abstract: Gas hydrates dominated by methane naturally occur in deep marine sediment along continental margins. These compounds form in pore space between the seafloor and a sub-bottom depth where appropriate stability conditions prevail. However, the amount and distribution of gas hydrate within this zone, and free gas below, can vary significantly at different locations. To understand this variability, we develop a one-dimensional numerical model that simulates the accumulation of gas hydrates in marine sediments due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(179 citation statements)
references
References 87 publications
(77 reference statements)
4
173
1
1
Order By: Relevance
“…11a), most likely because for such high POCar (sedimentation rates >70-100 cm/kyr) the residence time of organic matter within the GHSZ decreases significantly. Overall, this effect is in agreement with results of Davie and Buffet (2001) and Bhatnagar et al (2007).…”
Section: Derivation Of the Transfer Functionsupporting
confidence: 82%
See 1 more Smart Citation
“…11a), most likely because for such high POCar (sedimentation rates >70-100 cm/kyr) the residence time of organic matter within the GHSZ decreases significantly. Overall, this effect is in agreement with results of Davie and Buffet (2001) and Bhatnagar et al (2007).…”
Section: Derivation Of the Transfer Functionsupporting
confidence: 82%
“…The input and degradation of POC are critical parameters in this regard as they are the driving force for CH 4 formation (Davie and Buffett, 2001). Bhatnagar et al (2007) performed a rigorous numerical model study of LGF systems and found out that GH formation mainly depends on (i) the thickness of the GH stability zone (GHSZ), (ii) the Damkohler number, representing the ratio of methane production to methane diffusion, and (iii) the first Peclet number, representing the ratio of fluid advection to methane diffusion. While the GHSZ can be easily calculated, specifically the estimation of the rate of methane production is problematic, which makes the result of Bhatnagar et al (2007) difficult to use without applying models of the same complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the 7 × 10 6 km 3 estimate pertains to bathymetric conditions during the last glacial maximum. The rationale for using this bathymetry to discuss gas hydrate accumulation comes from considerations of sea level (hydrostatic pressure) and the relatively slow cycling time of CH 4 in gas hydrate systems (>10 000 yr; Davie and Buffett, 2001;Bhatnagar et al, 2007). Sea level during the Holocene is much higher than that spanning most of the late Pleistocene.…”
Section: Methane Masses In Present-day Marine Gas Hydrate Systemsmentioning
confidence: 99%
“…These assumptions turn equation (3) into an ordinary differential equation that we solve with a Laplace transform method (see Appendix A). This analytic solution is useful because the results are easily reproducible and because it complements the numerical solutions most commonly employed in this kind of modeling [e.g., Davie and Buffett, 2001;Bhatnagar et al, 2007;Sivan et al, 2007]. While numerical solutions are more flexible and do not require the assumptions made here, an analytic treatment is adequate for our purpose, which is to quantify the major effects of diffusion, burial, and solute generation or consumption on steady state concentrations and isotopic compositions.…”
Section: Modelingmentioning
confidence: 99%
“…[55] The argument of the exponential in equation (6) is a dimensionless Peclet number, which quantifies the relative importance of diffusion and burial by sedimentation at a rate w in a layer of thickness z SMT [Boudreau, 1997;Bhatnagar et al, 2007]:…”
Section: Do Smts Require Aom?mentioning
confidence: 99%